PERMUDAAN ALAM JENIS MERANTI (Shorea spp.) DI HUTAN ADAT PENGAJID DESA SAHAN KABUPATEN BENGKAYANG - Rizky, Prili; Manurung, Togar Fernando; Wulandari, Reine Suci (Universitas Tanjungpura, 2018)
Natural regeneration plays an important role in the forest ecosystem. Meranti (Shorea spp.) that is the genera of Dipterocarpaceae, grows in the lowlands. Pengajid customary forest at Sahan Bengkayang regency is a natural resource that is owned by the village community to meet the ecological and economic needs. The study aimed to determine the condition of natural forest regeneration at the seedling level, sapling and poles meranti (Shorea spp.) in thisforest. The method used the method of field survey by means of a line striped. The striped line is the combination of track method and plot method with a track width of 20 m and a length of each line of 500 m. The observation plot was made with a plot size of 10 m x 10 m for regeneration at the poles level, plot size of 5 m x 5 m for sapling regeneration, and with a plot size of 2 m x 2 m with for seedling level regeneration. Analysis of the data used were: important value index, type dominance index, species diversity index and species abundance index. The results of this research showed that the condition of all levels of natural regeneration is low. It showed that the dominancy of meranti species (important value index) for the seedlings, saplings and poles level were 47.71%, 24.56% and 44.95%, respectivelly. The dominance value of the meranti type for seedlings, the saplings dan poles level were 0.01, 0.001 and 0.005, respectivelly. Diversity of meranti( diversity index) for the seedlings, saplings and poles value were 0.33, 0.15 and 0.24, respectivelly. Meanwhile, Meranti type abundance index for seedling level is 0.16, sapling level is 0.08 and pole level is 0.13. Keywords: Meranti, Natural regeneration, Pengajid